Recurring OH Flares towards o Ceti – I. Location and structure of the 1990s' and 2010s' events. Issue 2 (22nd February 2017) - Etoka, S.; Gérard, E.; Richards, A. M. S.; Engels, D.; Brand, J.; Le Bertre, T.
Abstract: We present the analysis of the onset of the new 2010s OH flaring event detected in the OH ground-state main line at 1665 MHz towards o Ceti and compare its characteristics with those of the 1990s' flaring event. This is based on a series of complementary single-dish and interferometric observations both in OH and H2 O obtained with the Nançay Radio telescope, the Medicina and Effelsberg Telescopes, the European VLBI Network and (e)Multi-Element Radio Linked Interferometer Network. We compare the overall characteristics of o Ceti's flaring events with those that have been observed towards other thin-shell Miras, and explore the implication of these events with respect to the standard OH circumstellar-envelope model. The role of binarity in the specific characteristics of o Ceti's flaring events is also investigated. The flaring regions are found to be less than ∼400 ± 40 mas (i.e. ≤40 ± 4 au) either side of o Ceti, with seemingly no preferential location with respect to the direction to the companion Mira B. Contrary to the usual expectation that the OH maser zone is located outside the H2 O maser zone, the coincidence of the H2 O and OH maser velocities suggests that both emissions arise at similar distances from the star. The OH flaring characteristics of Mira are similar to those observed in various Mira variables before, supporting the earlier results that the regions where the transient OH maser emission occurs are different from the standard OH maser zone.